SITAMPAN (Sistem Taman Pintar) untuk meningkatkan Produktivitas Sayuran Organik pada Kelompok Wanita Tani (KWT) di Desa Nglanjuk - Putri, Rosalinda Ellysa; Ummara, Aulia; Sofani, Mohammad Taufik; Ikhsan, Ridhotu Nur; Ramadhany, Achmad Fajar; Permadi, Arjun; Setiawan, Agung; Reziqna, Ayu Rahma; Maulana, Aditya Rahman; Dewangga, Diaz Alegra Arif (STIE Pelita Nusantara, 2024)
The 2023 Ormawa Capacity Strengthening Program by the Electrical Engineering Student Association team focused on the implementation of smart farming in Nglanjuk Village, Cepu District, Blora, Central Java. Although the village is rich in natural resources, the low quality of human resources and the lack of technology utilization are obstacles. The research noted that the Kelompok Wanita Tani (KWT) faced difficulties in manual watering, a problem that needed to be addressed immediately. Therefore, the team designed a solution by presenting the SiTampan (Sistem Taman Pintar) tool that can control the plant watering pump through a smartphone. This program aims to implement smart farming, increase the efficiency of time and energy, and create KWT Nglanjuk Village that implements technology-based smart agriculture. Keywords : Smart Farming, SiTampan, Kelompok Wanita Tani, Ormawa Capacity Building.